S100B and the influence of seasonal variation. (18th May 2016) - Henriksson, Anders E.
Abstract: Background A blood test for S100B can be used to rule out intracranial complications after minor head injury and thereby reduce the need for computed tomography (CT) examinations. The aim of this study was to investigate the clinical importance of a possible influence of seasonal variation on S100B.Methods The individual seasonal variation of S100B in 69 healthy volunteers living at latitudes with extremely variable seasonal exposure to sunlight was investigated.Results The mean serum concentration of S100B was 13% higher in August than in February, but however, not statistically significant ( p = 0.068). A good agreement between summer and winter S100B values was confirmed by Bland-Altman analysis and a significant correlation ( r = 0.317, p = 0.008) was shown between summer and winter S100B values.Conclusion This study did not show any clinical importance of seasonal variation of S100B that may influence the decision of CT scanning patients with head injuries.